2016
DOI: 10.5500/wjt.v6.i2.291
|View full text |Cite
|
Sign up to set email alerts
|

Massive haemorrhage in liver transplantation: Consequences, prediction and management

Abstract: From its inception the success of liver transplantation has been associated with massive blood loss. Massive transfusion is classically defined as > 10 units of red blood cells within 24 h, but describing transfusion rates over a shorter period of time may reduce the potential for survival bias. Both massive haemorrhage and transfusion are associated with increased risk of mortality and morbidity (need for dialysis/surgical site infection) following liver transplantation although causality is difficult to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 144 publications
2
86
0
Order By: Relevance
“…Intraoperative blood loss is an established risk factor for mortality after LT in adults . In adult LTs, independent risk factors for intraoperative bleeding include the presence of ascites and INR ≥ 1.6 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intraoperative blood loss is an established risk factor for mortality after LT in adults . In adult LTs, independent risk factors for intraoperative bleeding include the presence of ascites and INR ≥ 1.6 .…”
Section: Discussionmentioning
confidence: 99%
“…In adult LTs, independent risk factors for intraoperative bleeding include the presence of ascites and INR ≥ 1.6 . Other studies have identified prolonged operative time, warm ischemia time, and bilirubin levels as significant risk factors for intraoperative transfusion requirement in adult LTs . Unfortunately, pediatric LT studies investigating these risk factors are limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Massive transfusion was defined as ≥10 units of red blood cells transfused within 24 hours of surgery(15), and intra- operative mortality was also recorded as an outcome.…”
Section: Methodsmentioning
confidence: 99%